Interactive Effects of Pesticides and Nutrients on Microbial Communities Responsible of Litter Decomposition in Streams - Rossi, Florent; Pesce, Stéphane; Mallet, Clarisse; Margoum, Christelle; Chaumot, Arnaud; Masson, Matthieu; Artigas, Joan (Frontiers in Microbiology, 2018)
Global contamination of streams by a large variety of compounds, such as nutrients and pesticides, may exert a high pressure on aquatic organisms, including microbial communities and their activity of organic matter decomposition. In this study, we assessed the potential interaction between nutrients and a fungicide and herbicide (tebuconazole (TBZ) and S-metolachlor (S-Met), respectively) at realistic environmental concentrations on the structure (biomass, diversity) and decomposition activity of fungal and bacterial communities (leaf decay rates, extracellular enzymatic activities) associated with Alnus glutinosa (Alnus) leaves. A 40-day microcosm experiment was used to combine two nutrient conditions (mesotrophic and eutrophic) with four pesticide treatments at a nominal concentrations of 15 µg L-1 (control, TBZ and S-Met, alone or mixed) following a 2 × 4 full factorial design. We also investigated resulting indirect effects on Gammarus fossarum feeding rates using leaves previously exposed to each of the treatments described above. Results showed interactive effects between nutrients and pesticides, only when nutrient (i.e. nitrogen and phosphorus) concentrations were the highest (eutrophic condition). Specifically, slight decreases in Alnus leaf decomposition rates were observed in channels exposed to TBZ (0.01119 days-1) and S-Met (0.01139 days-1) than in control ones (0.01334 days-1) that can partially be explained by changes in the structure of leaf-associated microbial communities. However, exposition to both TBZ and S-Met in mixture (MIX) lead to comparable decay rates to those exposed to the pesticides alone (0.01048 days-1), suggesting no interaction between these two compounds on microbial decomposition. Moreover, stimulation in ligninolytic activities (laccase and phenol oxidase) was observed in presence of the fungicide, possibly highlighting detoxification mechanisms employed by microbes. Such stimulation was not observed for laccase activity exposed to the MIX, suggesting antagonistic interaction of these two compounds on the ability of microbial communities to cope with stress by xenobiotics. Besides, no effects of the treatments were observed on leaf palatability for macroinvertebrates. Overall, the present study highlights that complex interactions between nutrients and xenobiotics in streams and resulting from global change can negatively affect microbial communities associated with leaf litter, although effects on higher trophic-level organisms remains unclear.